Analysis of misses in imaging of head and neck pathology by attending neuroradiologists at a single tertiary academic medical centre. Issue 10 (October 2021) - Ferguson, A.; Assadsangabi, R.; Chang, J.; Raslan, O.; Bobinski, M.; Bewley, A.; Dublin, A.; Latchaw, R.; Ivanovic, V.
Abstract : AIM: To analyse errors in head and neck (H&N) pathology made by attending neuroradiologists at a single tertiary-care centre. MATERIALS AND METHODS: A neuroradiology quality assurance (QA) database of radiological errors was searched for attending physician errors in H&N pathology from 2014–2020. Data were limited to computed tomography (CT) and magnetic resonance imaging (MRI) reports. Data were collected on missed pathologies and study types. Misses were grouped into three categories: central neck (thyroid gland, aerodigestive tract), lateral neck (salivary glands, lymph nodes, soft tissues), and face/orbits (orbits, sinuses, masticator space). RESULTS: During the study period, a total of 283, 248 CT and MRI neuroradiology examinations were interpreted (all indications). Seventy-four H&N misses were identified comprising 85.1% perceptual and 14.9% interpretive errors. The distribution of errors was face/orbits (37.8%), central neck (36.5%), and lateral neck (25.7%). Clinically significant errors were found most commonly in the aerodigestive tract (21%), orbits (17.7%), masticator space, and parotid glands (14.5% each). The majority (67.6%) of the misses were detected on examinations that were not performed for a primary H&N indication; MRI brain was the most common examination (27%). Clearly malignant or potentially malignant masses accounted for 48.6% of all misses. CONCLUSION: The majority of H&N misses were perceptual and were detected on examinations not performed for a H&N indication. Clearly malignant or potentially malignant masses represented half of all misses. Highlights: Errors were most common in the aerodigestive tract, orbits, and masticator space. 85.1% of errors were perceptual. Most misses were detected on exams not performed for a primary H&N indication. Clearly malignant or potentially malignant masses represent half of all misses. Search patterns including anatomic sites of common errors could decrease misses.